Prevalence and severity of non‐alcoholic fatty liver disease are underestimated in clinical practice: impact of a dedicated screening approach at a large university teaching hospital. Issue 1 (10th December 2017) - Marjot, T.; Sbardella, E.; Moolla, A.; Hazlehurst, J. M.; Tan, G. D.; Ainsworth, M.; Cobbold, J. F. L.; Tomlinson, J. W.
Abstract: Aims: To define the attitudes and current clinical practice of diabetes specialists with regard to non‐alcoholic fatty liver disease and, based on the results, implement an evidenced‐based pathway for non‐alcoholic fatty liver disease assessment. Methods: An online survey was disseminated to diabetes specialists. Based on findings from this survey, we sought a local solution by launching an awareness campaign and implementing a screening algorithm across all diabetes clinics at a secondary/tertiary referral centre. Results: A total of 133 diabetes specialists responded to the survey. Fewer than 5% of responders correctly assessed the prevalence and severity of advanced fibrotic non‐alcoholic fatty liver disease in people with diabetes as 50–75%. Whilst most clinicians performed liver function tests, only 5.7% responded stating that they would use, or had used, a non‐invasive algorithm to stage the severity of non‐alcoholic fatty liver disease. Implementing a local non‐alcoholic fatty liver disease awareness campaign and screening strategy using pre‐printed blood request forms, we ensured that 100% ( n =395) of all people with Type 1 and Type 2 diabetes mellitus attending secondary/tertiary care diabetes clinics over a 6‐month period were appropriately screened for advanced fibrotic non‐alcoholic fatty liver disease using the Fib‐4 index; 17.9% required further investigation or assessment. Conclusions: The prevalence and severity of non‐alcoholic fatty liver disease are underestimated among diabetes specialists. The Fib‐4 index can easily be incorporated into clinical practice in secondary/tertiary care to identify those individuals at risk of advanced fibrosis who require further assessment and who may benefit from a dedicated multidisciplinary approach to their management. What's new?: The prevalence and severity of non‐alcoholic fatty liver disease (NAFLD) in patients with diabetes are currently underestimated by diabetes specialists. Informative, non‐invasive scoring algorithms to stage NAFLD more accurately can be easily integrated into clinical practice in secondary/tertiary care. A total of 17.9% of people with diabetes who were attending diabetes clinics in a secondary/tertiary care setting were identified as either at indeterminate or high risk of advanced fibrotic NAFLD, and required additional investigation. A total of 63.6% of people with Type 2 diabetes requiring secondary/tertiary care,  who were identified as at indeterminate or high risk of advanced NAFLD on screening, had elevated liver stiffness evaluations. This equates to 13.1% of the people with Type 2 diabetes who needed hospital‐based care.